On the initiation and propagation of fatigue cracks in WC-Co - Erling, Ghita (My University, 1998)
This research examines fatigue in WC-Co, both under compressive and tensile loading conditions. A new macro-mechanism for compression fatigue crack propagation is put forward, which contradicts existing data on compression fatigue cracks as being self-limiting. Evidence of this macro-mechanism is presented in the form of final crack length versus number of cycles data, and micrographs of the compression fatigue cracks. A finite element study of the stress distribution in the WC-Co microstructure during compression fatigue loading has been developed. This model verifies possible methods of compression fatigue crack initiation. Examination of tensile fatigue and fast: fracture surfaces is used to show that fatigue is a separate mechanism to fast fracture in WC-Co. Characteristic features of the fatigue fracture surface are presented. A possible fatigue crack propagation mechanism is also presented. Finally, fatigue crack growth rate data in the form of the Paris equation is presented for WC-Co grades T6 and G6.
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Engineering, Johannesburg, 1998
Keywords: Materials--Fatigue; Strains and stresses; Structural failures; Strength of materials; Fatigue testing machines